Asas Retroaktif Dalam Pelaksanaan Surat Keputusan Pemberhentian Pensiunan Pegawai Negeri Sipil - Faisal, Faisal; A. Gani , Iskandar; Mahfud, Mahfud (Jurnal Suara Hukum, 2023)
This study aimed to examine the dishonorable discharge of retired civil servants by studying legal regulations and cases related to the dishonorable dischargeof retired civil servants. This study employed a normative juridical method with the legal approach, conceptual approach, and case approach. The finding showed that the dishonorable dischargedecree issued by the Head of Regional Office XIII of BKN (State Civil Service Body) of Banda Aceh Number: 23/KEP/KANREG-XIII/BKN/VIII/2016 on August 15, 2016, regarding the revocation/cancellation of the previous decision, followed by the Decree of the Regent of Aceh Barat Number: Peg.880/ 460/2017 on August 4, 2017, concerning the dishonorable discharge ascivil servants in the case of Tgk. Arwyzal ABM, ST. When this decree was issued,the person had been in retirement for seven months, meaning that this decree was applied retroactively. Keywords: Retroactive Principle; Discharge, State Civil Apparatus